Benzoyl Peroxide's Sensitisation Potential and Potency in Experimental Methods and Review of Contact Allergy and Allergic Contact Dermatitis - Egele, Kerstin; Drexler, Hans; Fartasch, Manigé; van Kampen, Vera; Merk, Hans F.; Nowak, Dennis; Schnuch, Axel; Uter, Wolfgang; Kreis, Patricia; Blömeke, Brunhilde (Contact Dermatitis, 2025)
Positive patch test responses to benzoyl peroxide (BPO) have been reported from patients without and with known exposure. Up to 6.5% were found in the United States and 7.8% in a study including patients from Germany, Austria and Switzerland. We provide an overview of the skin sensitisation potential and potency of BPO based on animal experiments and non-animal methods. BPO tested positive in Guinea Pig Tests and the Local Lymph Node Assay. Application of the current OECD guideline to identify a skin sensitizer by combining non-animal method results gave differing outcomes. Moreover, patch test responses of patients to BPO were considered to determine the importance of BPO as a relevant occupational contact allergen. Another well-known BPO exposure is the topical application to treat acne. Despite widespread use, extensive and long-term skin exposure, we found for this group only studies reporting few positive patch test reactions. Further, occupational handling of BPO and contact allergy is reported by dental technicians. In-depth evaluation of the prevalence of contact allergy in different professions with suspected BPO exposure did not reveal an association with occupational handling of BPO. Consequently, a generally increased risk for those professions is not supported.
CRIS-Team Scopus Importer:2025-02-14
Keywords: allergic contact dermatitis; benzoyl peroxide [CAS-no. 94-36-0]; non-animal methods; occupational allergen